SADI SHERAZI’S LIFESTYLE AND HIS WORKS: “GULISTON” AND “BOSTON” - Islomova Zulayho (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: This article is the about Sadii Shirazi and his works.This investigation was conducted by researching information about developmenting of Sherazi literature. As part of our article we have to focus on Sherazi literature.